Relationship between education, health and crime: fable, fallacy or fact - Kadri, Adeel Sultan
The study is an empirical evaluation of specific criminal activities. The relationship of criminal activities with inflation, unemployment, investment, education and health are examined through an annual data set from 1980 to 2007. To test the order of integration, Augmented Dickey Fuller test and Philips Perron are used. To find the evidences of long run relationship, Cointegrating Regression Durban Watson, Engle Granger two step procedure and Johansen and Juselis method is used. Results show that education and health have a positive and significant relationship with most of the criminal activities in the study. Another unusual finding is that inflation and unemployment are insignificant in case of two out of three crimes, however, investment is found highly significant and negatively related with these crimes. The study indicates that an educated, healthy and legally employed person can also be involved in unsophisticated blue collar criminal activities.Education; health; Crime